The Effect of Health Education With Playing Card Media on The Level of Students’s Knowledge About Vulva Hygiene - Dhita Aulia Octaviani; Adelia Rahma Anggraeni; Heny Rosiana (JURNAL KEBIDANAN, 2023)
Indonesia's humid and hot climate makes the body sweat excessively so that the pH of the vagina increases and facilitates the growth of bacteria in the vagina. So it takes enough knowledge for students to be able to care for the vagina to avoid reproductive health problems. Health information on vulva hygiene in boarding schools is very rare.  Improving students' knowledge can be done by providing health education using educational game media. The purpose of this study was to find out the effect of health education with card game media on the level of knowledge of vulva hygiene in students. This research was conducted at Askhabul Kahfi Islamic Boarding School from March until May 2021. This research included a pre-experimental design using one group pretest and posttest. The sample in this research was a grade IX junior high school student aged 14-16 years old (57 students). Sampling techniques used purposive sampling technique and data analysis used Wilcoxon Signed Rank Test. The results of the research that the average score of knowledge of the students before and after giving health education using card game media is 60.61 and 81.58. There was an average increase of before and after giving health education  20.97. The results of this research indicated that there was an influence between health education about vulva hygiene and card games on the knowledge level of students at the Askhabul Kahfi Islamic Boarding School with the Asymp.Sig value of 0.000 0.05. The benefit of this research for students of Askhabul Kahfi Islamic Boarding School will understand the material, will not underestimate the importance of vulva hygiene, and will do proper vulva hygiene after getting health education given by the researcher through card games.